Effect of individual preventive practices on COVID-19 infection: an analysis of big data collected at PCR testing centers in Hiroshima, Japan - Tatsuhiro Nagata; Odgerel Chimed-Ochir; Yui Yumiya; Junko Tanaka; Masao Kuwabara; Kanako Kitahara; Hiroki Ohge; Tatsuhiko Kubo (BMC Public Health)
Abstract Background By May 7, 2023, COVID-19 had significantly impacted Japan, with 33,728,909 infections and 74,663 deaths reported. Hiroshima Prefecture alone recorded 816,354 cases and 1,373 deaths. The World Health Organization emphasized the importance of non-pharmaceutical interventions (NPIs) for preventing infectious disease transmission. Individual NPIs, such as hand hygiene, mask wearing, and avoiding crowded places, comprise simple everyday measures that individuals can personally undertake to protect themselves and others from contracting and transmitting respiratory infections. Japan’s Cabinet Secretariat also recommended these measures. Previous studies investigated the effectiveness of NPIs but often used relatively short data-collection periods. Starting in May 2020, Hiroshima Prefecture adopted a unique COVID-19 public health surveillance policy that used standardized data-collection forms. The present analysis examines the association between individual NPIs and COVID-19 infections. Methods Data were collected at 14 PCR centers from April 1, 2021, to August 3, 2022 in Hiroshima Prefecture. Participants filled out the J-SPEED-style COVID-19 form, which included items on demographic information, job type, symptoms, and NPIs. The data were analyzed for demographic information, NPI compliance rates, infection rates in relation to NPI adoption, and adjusted risk ratios, which were obtained using a multivariate log-binomial regression model. Results A total of 1,125,188 tested cases from 4th to 7th waves were analyzed. Among the study population, the infection rate increased through the various waves, with the highest rate (8.3%) seen in the 7th wave. Adults aged 40–49 were most commonly tested, while those aged 60–69 had the lowest infection rates. Wearing masks/washing hands was the most commonly followed NPI. Compliance with NPIs decreased through the waves. Individuals adhering to NPIs had lower infection rates. The number of preventive measures adopted was correlated with a reduced infection risk. Conclusion This analysis provides evidence to guide COVID-19 prevention policies. Simultaneous adherence to multiple NPIs proved more effective in preventing COVID-19. Despite changes in viral strains and the number of infected cases, hand washing/mask wearing, refraining from travel, and refraining from dining out significantly associated with a reduction of COVID-19 infection. Our findings are likely to be applicable in future infectious disease outbreaks.